Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Review: 10



Work Step by Step

We are given that $f(x)=x^{2}-2$, $g(x)=x+1$, and $h(x)=x^{3}-x^{2}$. We know that $(h\circ h)(x)=h(h(x))$. Therefore, $(h\circ h)(2)=h(h(2))=h(2^{3}-2^{2})=h(8-4)=h(4)=4^{3}-4^{2}=64-16=48$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.